Perbandingan Metode Pemberian Pakan Tebar dan Titik Tengah Kolam Pada Budidaya Intensif Ikan Nila (Oreochromis niloticus) di PT. Superindo Sidoarjo - Muhammad Zunaini Alghazi; Ummul Firmani (Universitas Mataram, 2026)
This study aimed to analyze the effect of feeding methods on growth performance, feed efficiency, and survival rate of Nile tilapia (Oreochromis niloticus). Two feeding methods were compared: broadcast feeding and central point feeding. The experiment was conducted for seven weeks, and the observed parameters included absolute length growth, absolute weight growth, Feed Conversion Ratio (FCR), Survival Rate (SR), and water quality parameters (temperature, pH, salinity, EC, and TDS). Data were analyzed using descriptive quantitative methods. The results showed that the broadcast method produced more stable length and weight growth with FCR values ranging from 0.93 to 1.93. The central point method showed more fluctuating growth patterns, with lower FCR values in the early weeks (0.18–0.35) but higher variation in certain periods. Both methods resulted in a 100% survival rate. Water quality parameters in both treatments were within optimal and similar ranges, indicating that differences in production performance were mainly influenced by feed distribution strategy rather than environmental factors. Overall, the broadcast method supported more uniform growth, while the central point method potentially improved feed efficiency under certain conditions